Becoming Melungeon : Making an Ethnic Identity in the Appalachian South - Schrift, Melissa (UNP - Nebraska, 2013)
Appalachian legend describes a mysterious, multiethnic population of exotic, dark-skinned rogues called Melungeons who rejected the outside world and lived in the remote, rugged mountains in the farthest corner of northeast Tennessee. The allegedly unknown origins of these Melungeons are part of what drove this legend and generated myriad exotic origin theories. Though nobody self-identified as Melungeon before the 1960s, by the 1990s "Melungeonness" had become a full-fledged cultural phenomenon, resulting in a zealous online community and annual meetings where self-identified Melungeons gathered to discuss shared genealogy and history. Although Melungeons are commonly identified as the descendants of underclass whites, freed African Americans, and Native Americans, this ethnic identity is still largely a social construction based on local tradition, myth, and media. In this book, the author examines the ways in which the Melungeon ethnic identity has been socially constructed over time by various regional and national media, plays, and other forms of popular culture.